The PENGARUH NON NUTRITIVE SUCKING TERHADAP NYERI SELAMA PROSEDUR INVASIF PADA NEONATUS - Atik Pramesti Wilujeng; Ifada Suryaningsih (coba, 2021)
Background : Pain is a complex phenomenon most difficult to understand neonates. At the time the hospitalized neonates, one of the factors causing pain in neonates carried out invasive procedure. The purpose of this research is to know the effect of non nutritive sucking on pain during invasive procedure in neonates at Perinatologi of Genteng Hospital Banyuwangi 2016. Methods: This study used quasi experimental design with post test only non equivalent control group approach. The sampling technique used is non probability sampling with purposive sampling. The sample size in this study was 38 neonates which were divided into two groups consists of groups given NNS and groups not given NNS, each group consisted of 19 neonates. The instrument used to measure the dependent variable is the NIPS (Neonatal infant pain scale), then analyzed by U Mann-Whitney statistic test. Result: Mann-Whitney U test results showed p value <0.05 is 0.001 means there is influence of non nutritive sucking on neonatal pain during invasive procedure. Discussion: Provision of NNS proven to reduce pain as non-pharmacological pain management for neonates during invasive procedures.